Outubro no seio do movimento negro nos EUA: da revolução à política de concessões - Góes, Weber Lopes (Pontifícia Universidade Católica de São Paulo, 2017)
In this article, we examine the determinations that emerged from the movements of a socialist nature in the United States of America after the October Revolution of 1917. We intend to present roughly the forms of organization and the perspectives of social movements, trade unions and parties, namely: the fight against racism, racial discrimination and overcoming the order of capital. Finally, we present the strategies developed by the dominant American classes to overthrow the social movements in that country.